Single Anterior Crossbite Correction in Mixed Dentition Using Z’spring Along with Posterior Bite Plane: A Case Report - Ankita Sinha1, Susant Mohanty2 , Sonu Acharya3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Anterior cross bite is defined as “palatal positioning of the maxillary anterior teeth relative to the mandibularanterior teeth”.Various treatment options available are removable & fixed appliances. This is a case report ontreating a case of single anterior tooth crossbite during the mixed dentition using the “Hawley’s appliancewith posterior bite plane & Z’spring”. The active treatment time was 3 months in total & the treatmentoutcomes were followed up consequently for the next 4 months successfully